Evaluating the effectiveness of cybersecurity training: key elements, best strategies, and future prospects - Salem, Omran; Hamza, Marwa Fayiz; Khedher, Akram M Z M (IEEE, 2025)
Cybercrime methods are constantly evolving and increasing, which necessitates an urgent need to raise the level of individuals and enhance their security behavior, for fear of falling victim to these crimes. Hence, the need for training workshops to raise awareness of cybercrime has emerged. Accordingly, this research evaluates the effectiveness of these workshops by analyzing the results of the questionnaire of participants in these workshops before and after the workshops. The research discussed the most important strategies and evaluation models that can be used to improve these training programs. Based on the analysis of the questionnaire results, which showed a significant improvement in the awareness of participants, the research presented several recommendations aimed at increasing the effectiveness of these workshops in a way that ensures increased societal impact in combating cyber threats.